Morphological aspects of Paracoccidioides brasiliensis in lymph nodes : implications for the prolonged latency of paracoccidioidomycosis? (2000)
ABSTRACT: In order to determine if fungal morphology in tissues would furnish indications on the viability of Paracoccidioides brasiliensis yeast cells, lymph node biopsies from ve patients with paracoccidioidomycosis, including one with residual circumscribed lesions, were examined. A program that allows transferring of microscopic images to the computer for further processing was used. In the four active cases, the infected lymph nodes had over 49% of healthy-looking yeast cells while in the case of the residual lesion, this gure was smaller (21%). The residual had a larger proportion of aberrant yeast cells, with predominance of shell-like, empty cells (33%) and crescent bodies (30%); balloon-like yeasts were also seen (16%). The last two types of cells were also seen in the active lesions, but in smaller proportions, 58% and 59%, respectively. The number of multiple budding yeast cells, which clearly demonstrate fungal viability, ranged 24–33% in active cases but was only 5% in the residual lesion. Although the number of biopsies examined is small, the results tend to indicate that the morphology of P. brasiliensis yeast cells in walled-off tissues is abnormal and that the number of viable elements is small. There might be a connection between these ndings and the long latency period illustrated by those patients with paracoccidioidomycosis that have been diagnosed in non-endemic areas. Additionally, if P. brasiliensis yeast cells were to be subjected to the microaerophilic environment present in walled-off lesions, they would probably require a long time to multiply. Under these circumstances, the mycosis would also need many years to manifest.